(untitled) (Ciencias Veterinarias, 2019)
A descriptive study was carried out in 42 dairy farms, located in four geographical areas of Costa Rica, San Carlos, Zarcero, Cartago and Tilarán during 2001-2002. It includes the descrption of the infrastructure anda the sources of the water used for hygienic and operational procedures like handling and caring for the animals. At each farm, the cattle were bled to detect anti-Leptospira antibodies. Simultaneously each dairyman was surveyed to determine his/her potential exposure to the Leptospira spp. Infection, according to farm characteristics and the use of protective measures while handling the cattle, which were verified by observation. The statistical analysis was performed by the calculation of frequencies with a 95% confidence interval. The study population included 177 dairy workers, 87% male; their ages ranged from 11 to 78 years, with an average of 35. Eighty eight percent carryong out three or more activitiees with the animals and 79.0% adjudged to the presence of redents. Dairymen from Costa Rican farms are significantly exposed to he leptospirosis agent as they undertake their duties. The increases on account of environmental conditions and could become a serious halth problema if corrective measures are not taken for the exposure factors identified in this research.